Plasma concentrations of lysophosphatidic acid and the expression of its receptors in peripheral blood mononuclear cells are altered in patients with cocaine use disorders - María Flores-López; Nuria García-Marchena; Francisco J. Pavón-Morón; Nerea Requena-Ocaña; Laura Sánchez-Marín; Laura Martín-Chaves; Mónica García-Medina; Carmen Pedraza; Estela Castilla-Ortega; Juan J. Ruiz; Fernando Rodríguez de Fonseca; Pedro Araos; et al. (Translational Psychiatry, 2023)
Abstract We have recently reported alterations in the plasma concentrations of lysophosphatidic acid (LPA) in patients with substance use disorders. In order to further explore the potential role of the LPA signaling system as biomarker in cocaine use disorders (CUD) we conducted a cross-sectional study with 105 patients diagnosed with CUD and 92 healthy controls. Participants were clinically evaluated and blood samples were collected to determine plasma concentrations of total LPA and LPA species (16:0-, 18:0-, 18:1-, 18:2-, and 20:4-LPA), and the gene expression of LPA1 and LPA2 receptors in peripheral blood mononuclear cells. We found that patients with CUD had significantly lower plasma concentration of the majority of LPA species, while the mRNA expression of LPA1 receptor was found to be higher than controls. Moreover, we found a positive association between plasma concentration of 20:4-LPA and relevant CUD-related variables: age of onset cocaine use and length of cocaine abstinence. The statistical analysis revealed sex differences in concentrations of total LPA and LPA species, and women showed higher LPA concentrations than men. Furthermore, studies in rats of both sexes showed that plasma concentrations of total LPA were also altered after acute and chronic cocaine administration, revealing a sexual dimorphism in these effects. This study found alterations on the LPA signaling system in both, patients with CUD and rats treated with cocaine. Our results demonstrate that LPA signaling is impacted by CUD and sex, which must be taken into consideration in future studies evaluating LPA as a reliable biomarker for CUD.